Interventions to improve pharmaceutical care: Scope review (Research, Society and Development, 2024)
Objective: To map types of organizational, financial, professional, governmental/regulatory, and multifaceted interventions used to improve pharmaceutical services. Methodology: This is a scoping review. An appropriate method when literature mapping focused on a specific field of interest is required; with a time, frame between 2018 and 2023. Results: Two studies on political and regulatory interventions were retrieved; three on organizational interventions regarding the use of information and communication technologies; eight on organizational interventions regarding the planning and technical/clinical management of medicines; seven on professional interventions: aimed at professionals, users, and caregivers; three on financial interventions; five on multifaceted interventions. Conclusion: Finally, it can be inferred that professional, organizational, regulatory, financial, and multifaceted interventions have varied impacts on improving the technical management of pharmaceutical services and the clinical management of medicines; that is, on the provision of quality pharmaceutical services.